Long non‐coding RNA ELDR enhances oral cancer growth by promoting ILF3‐cyclin E1 signaling. (12th October 2020) - Sur, Subhayan; Nakanishi, Hiroshi; Steele, Robert; Zhang, Dapeng; Varvares, Mark A; Ray, Ratna B
Abstract: Oral squamous cell carcinoma (OSCC) is the sixth most common cancer with a 5‐year overall survival rate of 50%. Thus, there is a critical need to understand the disease process, and to identify improved therapeutic strategies. Previously, we found the long non‐coding RNA (lncRNA) EGFR long non‐coding downstream RNA (ELDR) induced in a mouse tongue cancer model; however, its functional role in human oral cancer remained unknown. Here, we show that ELDR is highly expressed in OSCC patient samples and in cell lines. Overexpression of ELDR in normal non‐tumorigenic oral keratinocytes induces cell proliferation, colony formation, and PCNA expression. We also show that ELDR depletion reduces OSCC cell proliferation and PCNA expression. Proteomics data identifies the RNA binding protein ILF3 as an interacting partner of ELDR. We further show that the ELDR‐ILF3 axis regulates Cyclin E1 expression and phosphorylation of the retinoblastoma (RB) protein. Intratumoral injection of ELDR‐specific siRNA reduces OSCC and PDX tumor growth in mice. These findings provide molecular insight into the role of ELDR in oral cancer and demonstrate that targeting ELDR has promising therapeutic potential. Synopsis: The long non‐coding RNA ELDR is upregulated in oral squamous cell carcinoma and promotes EGFR and ILF3‐Cyclin E1 signaling. Targeted depletion of ELDR reduces OSCC tumor growth in vivo . Long non‐coding RNA ELDR is upregulated in oral squamous cell carcinoma (OSCC) patients. LncRNA ELDR induces OSCC cell growth by inhibiting miR‐7 and inducing EGFR and ILF3‐CyclinE1 signaling. Intratumoral delivery of ELDR‐specific siRNA reduces OSCC xenograft tumor growth in a preclinical mouse model. Abstract : The long non‐coding RNA ELDR is upregulated in oral squamous cell carcinoma and promotes EGFR and ILF3‐Cyclin E1 signaling. Targeted depletion of ELDR reduces OSCC tumor growth in vivo .